2014
DOI: 10.1038/ncomms6563
|View full text |Cite
|
Sign up to set email alerts
|

The internal Cdc20 binding site in BubR1 facilitates both spindle assembly checkpoint signalling and silencing

Abstract: Improperly attached kinetochores activate the spindle assembly checkpoint (SAC) and by an unknown mechanism catalyse the binding of two checkpoint proteins, Mad2 and BubR1, to Cdc20 forming the mitotic checkpoint complex (MCC). Here, to address the functional role of Cdc20 kinetochore localization in the SAC, we delineate the molecular details of its interaction with kinetochores. We find that BubR1 recruits the bulk of Cdc20 to kinetochores through its internal Cdc20 binding domain (IC20BD). We show that prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 42 publications
4
60
1
Order By: Relevance
“…Most APC/C substrates are recruited by interaction with the seven-blade β-propeller WD40 repeat domain in the C-terminal half of the APC/C activator subunit (He et al, 2013). This domain contains binding pockets that recognize APC/C degrons, of which there are three major types: the destruction box (D box) (Glotzer et al, 1991), the KEN box (Pfleger and Kirschner, 2000) and the ABBA motif (Burton et al, 2011; Lischetti et al, 2014; Lu et al, 2014; Di Fiore et al, 2015; Diaz-Martinez et al, 2015) (Figure 1). A fourth sequence, the CRY motif, also binds the WD40 domain (Alfieri et al, 2016; Yamaguchi et al, 2016), but only a single instance (in Cdc20) has been identified to date (Reis et al, 2006).…”
Section: Substrate Recognition By the Apc/cmentioning
confidence: 99%
“…Most APC/C substrates are recruited by interaction with the seven-blade β-propeller WD40 repeat domain in the C-terminal half of the APC/C activator subunit (He et al, 2013). This domain contains binding pockets that recognize APC/C degrons, of which there are three major types: the destruction box (D box) (Glotzer et al, 1991), the KEN box (Pfleger and Kirschner, 2000) and the ABBA motif (Burton et al, 2011; Lischetti et al, 2014; Lu et al, 2014; Di Fiore et al, 2015; Diaz-Martinez et al, 2015) (Figure 1). A fourth sequence, the CRY motif, also binds the WD40 domain (Alfieri et al, 2016; Yamaguchi et al, 2016), but only a single instance (in Cdc20) has been identified to date (Reis et al, 2006).…”
Section: Substrate Recognition By the Apc/cmentioning
confidence: 99%
“…The yeast protein Acm1 utilizes a similar motif known as the 'A motif' in addition to its KEN box to interact with and thereby inhibit the CDC20 yeast ortholog Cdh1 (Enquist-Newman et al, 2008;He et al, 2013). Because recent reports have shown the existence of a similar motif in BUBR1 (dubbed the Phe box or ICDC20BD) that is important for a stable BUBR1-CDC20 interaction and for SAC activity (Diaz-Martinez et al, 2015;Lischetti et al, 2014), we tested whether this region in BUB1 is involved in the localization of CDC20 to kinetochores. CDC20 localizes strongly to kinetochores in nocodazole-treated cells, and this depends on BUB1 (Fig.…”
Section: ) Lap-bub1mentioning
confidence: 99%
“…Therefore, these data suggest that the Drosophila BubR1 KAN motif may have an important role in Cdc20/Fzy kinetochore recruitment. Interestingly, several studies reported the identification of additional conserved motifs in human BubR1: an internal Cdc20 binding domain (IC20BD), also named Phe-box (for its phenylalanine containing region), a D-box located downstream of the Phe-box and the ABBA motif which encompasses the Phe-box (Lischetti et al, 2014; Di Fiore et al, 2015; Diaz-Martinez et al, 2015). These motifs were shown to contribute to Cdc20 binding and its recruitment to kinetochores (Lischetti et al, 2014; Di Fiore et al, 2015), and, although they were not essential for the SAC per se, they appeared to make the SAC more efficient (Lischetti et al, 2014; Di Fiore et al, 2015; Diaz-Martinez et al, 2015).…”
Section: Resultsmentioning
confidence: 99%